A New Type of Magnetic Actuator Capable of Wall-Climbing Movement Using Inertia Force - H. Yaguchi; S. Sakuma; T. Kato (Journal of Engineering)
This paper proposes a new type of a magnetic actuator that operates on a resonance energy of a mass-spring model by using an electromagnetic force. The magnetic actuator is moved by the difference in an inertia force during one period of vibration. Experimental result demonstrates that a horizontal speed of the magnetic actuator was 7.4 mm/s with load mass of 50 g. We considered a method of a cable-free movement of the actuator by using two iron rails and four permanent magnets. The magnetic actuator is able to move stably a ceiling plane and a wall plane. This actuator is able to move on the plane of the magnetic materials only a function generator and a power amplifier.